PHILOSOPHICAL PRESUPPOSITIONS FOR CONSTRUCTION OF ESD PHENOMENON - Baranova, Jūratė (Acta Paedagogica Vilnensia, 2011)
Is philosophical thinking contributing, or challenging ESD phenomenon? It seems the first alternative of challenging is quite possible for the reason, that classical philosophical thinking leans on superiority of the human mind over nature, soul over the body. This idea of dualism between two principles – nature and soul and between hostility to the soul of the outside world was formulated by Descartes, followed also by Kant, Hegel, Sartre. The author of this paper suggests the new alternative to this dualism developed by two phenomenologists Lithuanian thinkers – Alphonso Lingis and Arvydas Šliogeris. Both of them are rather different. Šliogeris lives in Lithuania, he is a homelander, looking skeptically on travelers throught the world. Lingis is an emigrant. Living in United States of America, his ancesters emigrated from Lithuania long ago, he does not speak Lithuanian. And his possible realm of the world, his native land, is any part of the world. It could be Artics or Jungles, India, Sri Lanca, Indonesia, Philipines, Marocco, Argentine, Gvatemala or Peru, or any other country as well. In this sense Šliogeris and Lingis thoughts seem to be diverse and go in opposite directions. One is homebody – an ethnocentrist, the other one – a permanent traveler and a cosmopolitan. But namely these two possible alternative approaches to the world show the ways of overcoming the dualism of body and mind and suggest diverse conceptual possibilities for the Education for Sustainable development.
Keywords: Lingis; Šliogeris; education for sustainable development; philosophy